2020
DOI: 10.3389/fpubh.2020.600196
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation and Virus Tracing of a Measles Outbreak in Zhoushan Islands, China, 2019

Abstract: Background: Measles transmissions due to case importations challenge public health systems globally and herd immunities in all countries. In 2019, an imported measles case and its subsequently outbreak was found in the Zhoushan Islands. Here, the process of epidemiological investigation and virus tracing were summarized to provide references for the prevention and control of measles in the future.Materials and methods: The data on the demographic, epidemiological, and clinical manifestation of measles cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We performed phylogenetic analysis and found that the genotype of the measles virus in all three cases was D8, which circulates in China ( Figure 1 ) [ 13 , 14 ]. This outbreak resulted in 3 cases and 964 potential exposures, with 341 HCWs and 623 ER patients.…”
Section: Resultsmentioning
confidence: 99%
“…We performed phylogenetic analysis and found that the genotype of the measles virus in all three cases was D8, which circulates in China ( Figure 1 ) [ 13 , 14 ]. This outbreak resulted in 3 cases and 964 potential exposures, with 341 HCWs and 623 ER patients.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, small outbreaks of mumps, rubella, and pertussis have occurred in under-vaccinated communities around the world ( 23 , 24 ). Measles, another totally preventable disease, has flared up recently in the US, and other countries, from parents failing to vaccinate their children ( 25 , 26 ). Before the measles vaccine, an estimated 3–4 million cases, 48,000 hospitalizations, and 450 deaths occurred annually in the US ( 25 ).…”
Section: Vaccine Hesitancy: It's Nothing Newmentioning
confidence: 99%
“…These fear campaigns continue to threaten public health. In the US, in 1998 there were 89 cases of measles, and jumped over 14-times to 1,282 cases in 2019 ( 25 , 26 ). Prevention is key and complacency is the killer.…”
Section: Vaccine Hesitancy: It's Nothing Newmentioning
confidence: 99%
“…Concurrently, PTB's notifiable incidence rate was 47.76 per 100,000, accompanied by a reported mortality rate of 0.14 per 100,000 [4]. Mumps, scarlet fever, pertussis, rubella and measles followed suit, representing five RIDs with comparatively elevated annual incidence rates that often clustered within specific regions [5][6][7][8][9][10][11][12]. Furthermore, the emergence and re-emergence of RIDs in recent years underscore the need for strengthen surveillance to enable early warnings and swift, effective responses.…”
Section: Introductionmentioning
confidence: 99%